Saturday

April 19, 2014

April 19, 2014

Posted by **Jordan** on Tuesday, April 3, 2007 at 11:20pm.

4x^2+3y^2+8x-6y-5=0

Also, is this a ellipse or a circle?

first of all arrange the terms that appear to 'belong' together

4x^2 + 8x + 3y^2 - 6y = 5

factor out the 4 from the x terms and the 3 from the y terms

4(x^2 + 2x + ??) + 3(y^2 - 2y + ??)=5

take 1/2 the coefficient of the middle term, square it, then add it

4(x^2 + 2x + 1) + 3(y^2 - 2y + 1) = 5 + 4 + 3

notice I added the 1 inside the bracket which was multiplied by 4, so really I added 4, in the same way for the y terms I added 1 to the inside, but that was multiplied by 3, so really I added 3

that is why on the right side you see a 4 and a 3 added.

now express it in the standard form of an ELLIPSE

4(x+1)^2 + 3(y-1)^2 = 12

and finally divide every term by 12 to get

(x+1)^2 /3 + (y-1)^2 /4 = 1

which I hope you recognize as an ellipse and hope you can read off its properties

**Related Questions**

Mat 116 - Solve the system by graphing 8x-6=-18 6y-8x=18 divide 1 equation by 2 ...

math - Find the general form of the equation of the circle. Center at the point...

math - Q: Convert 4x^2 + 4y^2 -8x -16y -29 = 0 into standard form. I first ...

Algebra - Solve. 8x-(4x+5)=7 8x-1(4x+5)=7 8x-4x-5=7 4x-5+5=7+5 4x=12 x=3. Is ...

Algebra 2 - Choose the appropriate simplified expression. 1. 8x^2-10x+3/6x^2+3x-...

For MathMate - Hi! So i posted a question yesterday and I worked on but before i...

Math - how an I tell if this is a circle or an ellipse? also, how am I supposed ...

math - The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct? [(2x...

math - 4 [(4x^2 + 4x)]^2 + 4(4x^2 + 4x) I got up to: 16 ( 4x^4 + 8x^3 + 5x^2 + x...

Math - Transform the equation by completing the square: 4x^2 + y^2 - 8x + 6y -3...